2007
DOI: 10.1111/j.1365-246x.2007.03545.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties as indicators of heavy metals pollution in urban topsoils: a case study from the city of Luoyang, China

Abstract: S U M M A R YThis paper deals with the magnetic properties [magnetic susceptibility, saturation isothermal remanent magnetization (SIRM), magnetomineralogicl parameters], the contents of heavy metals (Fe, Mn, Cd, Cr, Cu, Pb and Zn) and their mutual relationship in the urban topsoils of Luoyang, China. Magnetic susceptibility measured on 215 urban topsoil samples ranged from 31 × 10 −8 to 1128 × 10 −8 m 3 kg −1 (average 215 × 10 −8 m 3 kg −1 ) and showed that high magnetic susceptibility values were obtained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 52 publications
6
47
0
1
Order By: Relevance
“…Our previous study showed that significant correlation between magnetic properties (χlf and SIRM) and heavy metal contents (Cd, Cu. Pb and Zn) existed in urban soils (Lu and Bai 2006;Lu et al 2007). In order to establish the correlation of heavy metal content and magnetic concentration-related parameters, linear regression analysis were done for the soil samples from Zone I, Zone II, and suburban and rural areas (Zones III-VIII), respectively.…”
Section: Associations Of Heavy Metals With Magnetic Propertiesmentioning
confidence: 99%
“…Our previous study showed that significant correlation between magnetic properties (χlf and SIRM) and heavy metal contents (Cd, Cu. Pb and Zn) existed in urban soils (Lu and Bai 2006;Lu et al 2007). In order to establish the correlation of heavy metal content and magnetic concentration-related parameters, linear regression analysis were done for the soil samples from Zone I, Zone II, and suburban and rural areas (Zones III-VIII), respectively.…”
Section: Associations Of Heavy Metals With Magnetic Propertiesmentioning
confidence: 99%
“…Magnetic properties of marine sediments can often contribute reliable information on environmental change (Kumar et al 2005;Sangode et al 2007;Yang et al 2008;Alagarsamy 2009;Zheng et al 2010) and magnetic parameters such as magnetic susceptibility (MS) became a kind of basic data for marine sediment research (Evans and Heller 2003;Yim et al 2004;Ghilardi et al 2008;Meena et al 2011). As a fast and cost-effective parameter, MS also has been successfully used as a proxy for the detection of anthropogenic pollution caused by metallurgical dusts, fly ashes from power plants and urban airborne particulates (Bityukova et al 1999;Jordanova et al 2003;Gautam et al 2004;Lu et al 2007). Furthermore, previous studies have shown the potential of magnetic properties for assessment of pollution in coastal areas (Plater et al 1998;Plater and Appleby 2004;Ridgway and Shimmield 2002;Martins et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of other applications of magnetic properties for assessing soils, such as for hydric soil delineation (de Jong 2002;Grimley et al 2004) or soil pollution assessment (e.g. Kapička et al 2003Magiera et al 2006;Lu et al 2007;Kodešová et al 2011;Dlouhá et al 2013).…”
mentioning
confidence: 99%